2002
DOI: 10.1046/j.0300-9475.2002.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oral Tolerance with Micro‐Doses of Ovomucoid Depends on the Length of the Feeding Period

Abstract: Oral administration of antigen induces antigen-specific immunologic tolerance, which is known to be dose-dependent. We studied the influence of continuous oral administration of nanogram and microgram doses of antigen on oral tolerance induction. Mice were continuously exposed to varying doses (1 ngÀ1 mg/day) of ovomucoid (OM) for a minimum of 30 days and a maximum of 100 days. It was possible to induce oral tolerance measured as reduced proliferation and antibody production (immunoglobulin (Ig)G 1 , IgG 2a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…At the outset of the experiments, we determined the actual KSTI exposure of the F0 mice fed the standard soy-containing diet by analyzing the KSTI content in food sample extracts using a very sensitive ELISA. The content of KSTI in different food batches was found to be at microgram levels (31 ± 14 µg/g) corresponding to a daily intake of approximately 100–200 µg KSTI for the F0 mice, which in terms of oral tolerance induction is to be considered a prolonged low dose exposure [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…At the outset of the experiments, we determined the actual KSTI exposure of the F0 mice fed the standard soy-containing diet by analyzing the KSTI content in food sample extracts using a very sensitive ELISA. The content of KSTI in different food batches was found to be at microgram levels (31 ± 14 µg/g) corresponding to a daily intake of approximately 100–200 µg KSTI for the F0 mice, which in terms of oral tolerance induction is to be considered a prolonged low dose exposure [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…In this study, it is difficult to draw firm conclusions concerning the immunological effect of small amounts of BLG (approximately 1 µg/g) in such diets as we could not compare the responses to those of mice bred on a strictly antigen-free diet. Only a few studies have focused on the effect of feeding low doses of antigens to experimental animals bred on a strictly antigen-free diet [26, 27, 28]. Applying the same experimental protocol for the detection of oral tolerance, following the administration of ovomucoid to BALB/c mice in the drinking water, we found in a previous study the threshold for tolerance induction to be in the range of 0.1 mg of ovomucoid/day for 50 days [28].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have focused on the effect of feeding low doses of antigens to experimental animals bred on a strictly antigen-free diet [26, 27, 28]. Applying the same experimental protocol for the detection of oral tolerance, following the administration of ovomucoid to BALB/c mice in the drinking water, we found in a previous study the threshold for tolerance induction to be in the range of 0.1 mg of ovomucoid/day for 50 days [28]. Neither tolerance nor priming were observed at lower antigen doses, supporting the present findings that ingestion of an amount of BLG of approximately 5 µg/day does not affect the immune response to BLG in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plenty of reports have shown that digested formulas can stimulate the gut immune system towards induction of tolerance in newborns with an elevated risk of allergies (22,23). However, there have been only a few reports addressing the effect of nutritional status on oral tolerance (15, 24) and vir- ) were prepared as described in "Materials and Methods."…”
Section: Discussionmentioning
confidence: 99%